2014
DOI: 10.1503/jpn.130080
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neural correlates of self-focused emotion regulation in social anxiety disorder

Abstract: IntroductionEmotions are proposed to involve a "person-situation interaction that engages attention, has meaning to an individual, and causes a coordinated yet malleable multisystem response to the interaction," 1 including a subjectively experienced feeling component.2 Emotion regulation refers to processes that alter the nature, magnitude and duration of these multisystem responses and feelings.3 Once placed in an emotion-evoking situation, an individual can deploy attentional mechanisms for emotion regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 48 publications
7
46
2
1
Order By: Relevance
“…Across these studies, there is a general trend for disrupted (increased or decreased) levels of activity in prefrontal regions (dorsolateral and ventrolateral prefrontal cortex, dl/vlPFC, dorsal anterior cingulate cortex, dACC) among individuals with SAD, relative to healthy control participants when explicitly instructed to engage in a regulatory strategy (for recent meta-analyses, see BrĂĽhl et al, 2014; Zilverstand et al, 2016). However, findings are not entirely consistent, with two recent studies demonstrated no significant differences in prefrontal activity during regulation between groups of SAD and healthy control participants (Burklund et al, 2015; Gaebler et al, 2014). …”
Section: Introductioncontrasting
confidence: 64%
“…Across these studies, there is a general trend for disrupted (increased or decreased) levels of activity in prefrontal regions (dorsolateral and ventrolateral prefrontal cortex, dl/vlPFC, dorsal anterior cingulate cortex, dACC) among individuals with SAD, relative to healthy control participants when explicitly instructed to engage in a regulatory strategy (for recent meta-analyses, see BrĂĽhl et al, 2014; Zilverstand et al, 2016). However, findings are not entirely consistent, with two recent studies demonstrated no significant differences in prefrontal activity during regulation between groups of SAD and healthy control participants (Burklund et al, 2015; Gaebler et al, 2014). …”
Section: Introductioncontrasting
confidence: 64%
“…For one, OXT could be magnifying effects related to the neural integration of pain and threat (Shackman et al, 2011). In patients with SAD, which is characterized in part by an increased sensitivity to social signals, pMCC activation typically occurs in response to threat stimuli (Gaebler et al, 2014), which could suggest a similar mechanism to OXT, namely, that increased sensitivity to social stimuli takes place in the pMCC. Another reason could be the hypothesized role of this region in 'orienting the body toward innocuous and noxious somatosensory stimuli' (Vogt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For neuroimaging data, brain regions with significant task*group interactions for the regulation versus watch contrast were reported for downregulation (REDUCE) and upregulation (INCREASE). Unilateral effects were marked with (L) = left and (R) = right, all other effects were observed bilaterally. The following studies are marked in the Analysis column: studies where the task*interaction was not significant and group differences during the regulation condition were reported (marked with â—‡); studies that applied ad hoc correction with a fixed cluster threshold and voxelwise thresholds: p<0.001, p<0.005 (marked with <<<); studies performing ROI analysis with multiple comparison correction (marked with <<); studies that performed an additional ROI analysis of the amygdala without multiple comparison correction (marked with α); studies using cluster-size thresholding with a lenient voxelwise threshold (p<0.01, p<0.05) (marked with an <); all other studies employing either cluster-size thresholding (p<0.05) with voxelwise threshold (p<0.005), Gaussian Random fields correction (p<0.05), or FWE corrected whole-brain correction (p<0.05) are not marked. Abbreviations: IAPS = International Affective Picture System; NEG = negative/unpleasant, POS = positive/pleasant; LPP = Late positive potential MDD = Major Depressive Disorder, rMDD = remitted Major Depressive Disorder, BD = Bipolar Disorder, PTSD = Posttraumatic Stress Disorder, GAD = Generalized Anxiety Disorder, SAD = Social Anxiety Disorder, PD = Panic Disorder, OCD = Obsessive Compulsive Disorder, CUD = Cocaine use Disorder, ND = Nicotine Dependence, Sz = Schizophrenia, BPD = Borderline Personality Disorder, AvPD = Avoidant Personality Disorder Brain regions: aPFC = anterior prefrontal cortex, dACC = dorsal anterior cingulate, dlPFC = dorsolateral prefrontal cortex, dmPFC = dorsomedial prefrontal cortex, mPFC = medial prefrontal cortex, NAcc = nucleus accumbens, rACC = rostral anterior cingulate, OFC = orbitofrontal cortex, PCC = posterior cingulate cortex, SMA = supplementary motor area, vlPFC = ventrolateral prefrontal cortex, vmPFC = ventromedial prefrontal cortex A list of the included studies is provided in Supplementary Material 1 (Albein-Urios et al, 2014; Beauregard, Paquette, & LĂ©vesque, 2006; Blair et al, 2012; Davis et al, 2014; Denny et al, 2015; Dillon & Pizzagalli, 2013; Erk et al, 2010; Gaebler, Daniels, Lamke, Fydrich, & Walter, 2014; Goldin, Manber, Hakimi, Canli, & Gross, 2009; Goldin, Manber-Ball, Werner, Heimberg, & Gross, 2009; Greening, Osuch, Williamson, & Mitchell, 2014; Heller et al, 2009; Johnstone, van Reekum, Urry, Kalin, & Davidson, 2007; P Kanske, Schönfelder, Forneck, & Wessa, 2015; Philipp Kanske, Heissler, Schönfelder, & Wessa, 2012; Koenigsberg et al, 2009; S. Lang et al, 2012; Manber-Ball, Ramsawh, Campbell-Sills, Paulus, & Stein, 2013; Marissen, Meuleman, & Franken, 2010; Morris, Sparks, Mitchell, Weickert, & Green, 2012; New et al, 2009; Paul, Simon, Endrass, & Kathmann, 2015; Rabinak et al, 2014; Reinecke et al, 2015; …”
Section: Figurementioning
confidence: 99%
“…A list of the included studies is provided in Supplementary Material 1 (Albein-Urios et al, 2014; Beauregard, Paquette, & LĂ©vesque, 2006; Blair et al, 2012; Davis et al, 2014; Denny et al, 2015; Dillon & Pizzagalli, 2013; Erk et al, 2010; Gaebler, Daniels, Lamke, Fydrich, & Walter, 2014; Goldin, Manber, Hakimi, Canli, & Gross, 2009; Goldin, Manber-Ball, Werner, Heimberg, & Gross, 2009; Greening, Osuch, Williamson, & Mitchell, 2014; Heller et al, 2009; Johnstone, van Reekum, Urry, Kalin, & Davidson, 2007; P Kanske, Schönfelder, Forneck, & Wessa, 2015; Philipp Kanske, Heissler, Schönfelder, & Wessa, 2012; Koenigsberg et al, 2009; S. Lang et al, 2012; Manber-Ball, Ramsawh, Campbell-Sills, Paulus, & Stein, 2013; Marissen, Meuleman, & Franken, 2010; Morris, Sparks, Mitchell, Weickert, & Green, 2012; New et al, 2009; Paul, Simon, Endrass, & Kathmann, 2015; Rabinak et al, 2014; Reinecke et al, 2015; Reinecke, Thilo, Filippini, Croft, & Harmer, 2014; Schulze et al, 2011; Smoski, Keng, Schiller, Minkel, & Dichter, 2013; Townsend et al, 2013; van der Meer et al, 2014; Wang et al, 2014; Woodward et al, 2015; Wu et al, 2015; Ziv, Goldin, Jazaieri, Hahn, & Gross, 2013).…”
Section: Figurementioning
confidence: 99%